(untitled) (Conferencea, 2024)
As we all know, it is related to introducing students to new technologies, making their learning process more effective and creating an environment for their creativity and practice. This article shows what methods are used to form students’ readiness to use reversive and immersive technologies in the educational process and how they affect the development of students’ creativity, analysis, and practices. This article, which reveals the topic of students’ readiness to use reversive and immersive technologies in the educational process, can be widely used by students as well as independent researchers.